The Effect of High Intensity Interval Training on the Cardiovascular Endurance of Futsal Players at SMAN 1 Dompu in 2023 - Nurdin Nurdin (Lembaga Penelitian dan Pendidikan Mandala, 2025)
This study aims to determine the effect of high intensity interval training on the cardiovascular endurance of SMAN 1 Dompu futsal players in 2023. This study is a quasi-experimental study using a variety of HIIT exercises to improve cardiovascular endurance with a design of